2017
DOI: 10.26727/njrcm.2017.6.4.288-94
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence of Depression and its Associated Factors among the Elderly in Kancheepuram District, South India

Abstract: Background: The proportion of the elderly persons is increasing, most of the people lives in rural areas and depression among the elderly impairs the functioning in daily life. As people age, they experience multiple chronic health problems. Health problems when compounded with depression, worsens the clinical outcome still further. Objectives:To assess the prevalence of depression and its associated factors among the elderly. Materials and methods: This is a part of a larger study, conducted as a community ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…(8,9,15) We observed that depression was associated more with female gender and widowed status. Similar findings were reported from studies in India (17,18,19) and abroad. (20) The findings highlight the fact that elderly women need special attention.…”
Section: Resultssupporting
confidence: 91%
“…(8,9,15) We observed that depression was associated more with female gender and widowed status. Similar findings were reported from studies in India (17,18,19) and abroad. (20) The findings highlight the fact that elderly women need special attention.…”
Section: Resultssupporting
confidence: 91%
“…Pushparani et al, in their study among the elderly in Kancheepuram district of Tamil Nadu observed that 33.9% had mild and 13.8% had severe depression. 7 These findings are similar to our study where mild depression is more in study population than severe depression. In the current study, the proportion of female respondents with mild (38.1%) and severe (17.3%) depressive symptoms was more than the percentage of male respondents (31.6% &13.9% respectively).…”
Section: Discussionsupporting
confidence: 82%
“…Pushparani et al, in their study among the elderly in Kancheepuram district of Tamil Nadu, Ravindra et al in elderly population of urban Bangalore and D'Souza et al found the prevalence of depression to be 47.8%,44.8% and 51.9% respectively. [7][8][9] The results of these studies are in consonance to our study. However, Mandolikar et al conducted a study in urban area of Dakshina Kannada district of Karnataka and found the prevalence of depression among the elderly to be 75.5%.…”
Section: Discussionsupporting
confidence: 81%
“…It is also associated with greater role-function impairments, poor self-care and isolation decreased the ability to follow lifestyle recommendations, thus hindering the treatment of other medical conditions. Pushparni et al (2017) note the correlation between worsening outcomes for the treatment of older people with comorbid health issues when depression is present. In their study of nearly 500 older adults, 47% of those people were assessed as being depressed.…”
Section: Depression and Old Agementioning
confidence: 99%